Masterful coaching : inspire an impossible future while producing extraordinary leaders and extraordinary results - Hargrove, Robert A., 1947- 4 0 16; 5 (San Francisco, California : Jossey-Bass/Pfeiffer, 2003)
Introduces a coaching method designed to empower people to transform who they are as leaders while producing extraordinary results.
Includes bibliographical references and index.
Adult
Keywords: 2 -- 0; 6; Training of. -- Teams in the workplace.;Industrial efficiency.;Employee motivation.;Employees;Group relations training.;Motivation (Psychology); 20; 2